2017
DOI: 10.1007/s10753-017-0630-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Licochalcone A on IL-1β-Stimulated Human Osteoarthritis Chondrocytes

Abstract: Licochalcone A (Lico A), a flavonoid found in licorice root (Glycyrrhiza glabra), has been reported to have anti-inflammatory activity. In this study, we evaluated the anti-inflammatory effects of Lico A on IL-1β-stimulated human osteoarthritis chondrocytes and investigated the possible mechanism. Results demonstrated that Lico A treatment significantly inhibited PGE2 and NO production induced by IL-1β. IL-1β-induced iNOS and COX-2 expression were also inhibited by Lico A. Lico A inhibited MMP1, MMP3, and MMP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 33 publications
2
49
0
1
Order By: Relevance
“…As the component of HSDTT, Atractylodes lancea (Thumb. )DC not only reduce the expression of in ammatory cytokines in serum, but also decreases the expression of beclin-1 protein in synovial tissue of rat [28].Moreover, Radix Angelicae pubescentis and licorice all have a great effect on alliviating in ammtory ,and Radix Angelicae pubescentis has been shown to relieve pain by inhibiting the expression of TNF-α and IL-1β [29,30]. Angelicae Sinensis Radix inhibits apoptosis of chondrocyte via suppressing JNK and p38MAPK pathways [31].…”
Section: Discussionmentioning
confidence: 99%
“…As the component of HSDTT, Atractylodes lancea (Thumb. )DC not only reduce the expression of in ammatory cytokines in serum, but also decreases the expression of beclin-1 protein in synovial tissue of rat [28].Moreover, Radix Angelicae pubescentis and licorice all have a great effect on alliviating in ammtory ,and Radix Angelicae pubescentis has been shown to relieve pain by inhibiting the expression of TNF-α and IL-1β [29,30]. Angelicae Sinensis Radix inhibits apoptosis of chondrocyte via suppressing JNK and p38MAPK pathways [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although studies associated with the biological effects of Lico-E have reported lower efficacy than that of Lico-A, the biological effects of both licochalcones exhibit similar properties. According to recently reported studies associated with Lico-A, various biological effects such as neuroprotective [26], chondroprotective [27,28], antithrombotic [29], antimicrobial [30], and antiviral activities [30] have been reported. In addition, recent studies have also reported reduction in chronic allergic contact dermatitis as well as antidiabetic, anti-inflammatory, and antimicrobial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Licochalcone A reduced LPS-induced NF-κB transactivation by inhibiting phosphorylation of p65 at serine 276 and interaction of p65 with p300 [72]. e compound not only indicated an anti-inflammatory effect on IL-1β-stimulated chondrocytes by activating the Nrf2 signaling pathway [73] but also activated Keap1-Nrf2 signaling to inhibit arthritis by enhancing phosphorylation and expression of p62 at serine 349 [74]. ERK and p38 signaling pathways might play a role in attenuation of allergic airway inflammation by licochalcone A [75].…”
Section: Anti-inflammatory Activitymentioning
confidence: 91%